Tailored Surface Treatment of 3D Printed Porous Ti6Al4V by Microarc Oxidation for Enhanced Osseointegration via Optimized Bone In-Growth Patterns and Interlocked Bone/Implant Interface - Xiu, Peng; Jia, Zhaojun; Lv, Jia; Yin, Chuan; Cheng, Yan; Zhang, Ke; Song, Chunli; Leng, Huijie; Zheng, Yufeng; Cai, Hong; Liu, Zhongjun (ACS applied materials & interfaces, 2016)
3D printed porous titanium (Ti) holds enormous potential for load-bearing orthopedic applications. Although the 3D printing technique has good control over the macro-sturctures of porous Ti, the surface properties that affect tissue response are beyond its control, adding the need for tailored surface treatment to improve its osseointegration capacity. Here, the one step microarc oxidation (MAO) process was applied to a 3D printed porous Ti6Al4V (Ti64) scaffold to endow the scaffold with a homogeneous layer of microporous TiO2 and significant amounts of amorphous calcium-phosphate. Following the treatment, the porous Ti64 scaffolds exhibited a drastically improved apatite forming ability, cyto-compatibility, and alkaline phosphatase activity. In vivo test in a rabbit model showed that the bone in-growth at the untreated scaffold was in a pattern of distance osteogenesis by which bone formed only at the periphery of the scaffold. In contrast, the bone in-growth at the MAO-treated scaffold exhibited a pattern of contact osteogenesis by which bone formed in situ on the entire surface of the scaffold. This pattern of bone in-growth significantly increased bone formation both in and around the scaffold possibly through enhancement of bone formation and disruption of bone remodeling. Moreover, the implant surface of the MAO-treated scaffold interlocked with the bone tissues through the fabricated microporous topographies to generate a stronger bone/implant interface. The increased osteoinetegration strength was further proven by a push out test. MAO exhibits a high efficiency in the enhancement of osteointegration of porous Ti64 via optimizing the patterns of bone in-growth and bone/implant interlocking. Therefore, post-treatment of 3D printed porous Ti64 with MAO technology might open up several possibilities for the development of bioactive customized implants in orthopedic applications.